2015
DOI: 10.1021/acssuschemeng.5b01400
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hydrogels Prepared with Ionic-Liquid-Isolated vs Commercial Chitin and Cellulose

Abstract: Physical and/or covalently linked (chemical) hydrogels were prepared from chitin and cellulose extracted with ionic liquid from shrimp shells and wood biomass, respectively, and compared with hydrogels prepared from commercially available biopolymers, practical grade chitin, and microcrystalline cellulose. The highly porous aerogels were formed by initial dissolution of the biopolymers in NaOH/urea aqueous systems using freeze/thaw cycles, followed by thermal treatment (with or without epichlorohydrin as a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 64 publications
4
70
0
Order By: Relevance
“…Even then the resulting fibers were rough, non‐uniform, and of micrometer size. We previously related this to the lack of polymer‐chain entanglement at lower concentrations owing to the low molecular weight of PG‐chitin, which was confirmed by evaluation of other materials prepared from PG‐chitin solution …”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Even then the resulting fibers were rough, non‐uniform, and of micrometer size. We previously related this to the lack of polymer‐chain entanglement at lower concentrations owing to the low molecular weight of PG‐chitin, which was confirmed by evaluation of other materials prepared from PG‐chitin solution …”
Section: Resultsmentioning
confidence: 68%
“…Given the ability of ionic liquids (ILs) to dissolve essentially every type of renewable biomass to some extent, it is possible to cast otherwise insoluble polymers into virtually any architecture by utilizing their existing functions and properties [such as natural molecular weight (MW) and hydrogen bonding] in materials preparation . It was reported that a few biopolymers (mostly cellulose) were wet‐electrospun from nonvolatile ILs by directing the nonvolatile solution into a coagulation water bath .…”
Section: Introductionmentioning
confidence: 99%
“…The virtually unlimited possible combinations of their constituents allow for the fine-tuning of these properties and for the tailoring of ILs to address specific problems. For all these reasons, the ILs research field is still expanding and encompasses, but is not limited to, their study as suitable green substitutes of volatile organic compounds (VOCs), [1] as exceptional media to dissolve and functionalize biopolymers (cellulose, chitin, lignin and so on) [2][3][4][5][6][7] or capture CO2, [8,9] and as reagents or catalysts of some reactions. With regard to the latter, a new generation of ILs, characterized by at least an additional functional group either on the cation or on the anion directly involved in the reaction step, has been developed [task-specific ionic liquids (TSILs)].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely utilized in medical supplies (Sowmya et al 2011;Izumi et al 2015), cosmetics (Gautier et al 2008), and food (Han et al 1999) because its acetamide group located at the C2 position strongly affects the biochemical properties of chitin Madhumathi et al 2009). Chitin has been studied in various forms, including the hydrogel one (Tamura et al 2006;Mushi et al 2016), which can be prepared by chemical cross-linking (Chang et al 2011), immersion into alkaline solution , and recrystallization from solution (Shen et al 2016). However, these methods also have the following disadvantages: (1) a complicated organic synthesis procedure due to the existence of multiple steps; (2) environmental contamination caused by organic, acidic, and alkaline waste liquids; and (3) high cytotoxicity of the utilized chemical reagents.…”
Section: Introductionmentioning
confidence: 99%